Normal and hypoacoustic infant cry signal classification using time-frequency analysis and general regression neural network - Hariharan, Muthusamy, Dr.; Sindhu, R; Sazali, Yaacob, Prof. Dr. (Elsevier Ireland Ltd., 2012)
Link to publisher's homepage at http://www.elsevier.com/